Leviticus as literature - Douglas, Mary, 1921-2007 (Oxford University Press, 2000)
This first full-scale account of Leviticus by a world renowned anthropologist presents the biblical work as a literary masterpiece. Seen in an anthropological perspective Leviticus has a mystical structure which plots the book into three parts corresponding to the three parts of the desert tabernacle, both corresponding to the parts of Mount Sinai. This completely new reading transforms the interpretation of the purity laws. The pig and other forbidden animals are not abhorrent, they command the same respect due to all God's creatures. Boldly challenging several traditions of Bible criticism, M.